2023
DOI: 10.3389/fgene.2023.1248697
|View full text |Cite|
|
Sign up to set email alerts
|

Unravelling the genetic framework associated with grain quality and yield-related traits in maize (Zea mays L.)

Abstract: Maize serves as a crucial nutrient reservoir for a significant portion of the global population. However, to effectively address the growing world population’s hidden hunger, it is essential to focus on two key aspects: biofortification of maize and improving its yield potential through advanced breeding techniques. Moreover, the coordination of multiple targets within a single breeding program poses a complex challenge. This study compiled mapping studies conducted over the past decade, identifying quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Traits contributing to yield and grain quality are usually antagonistic to each other, and when applying various modifications in agrotechnology, this should be taken into consideration. The forms and amounts of available mineral nutrients in the soil can cause significant changes in the growth character and biochemical composition of plants [55]. According to Gu et al [56], the availability of N reduces oil concentration, while the application of K increases oil content.…”
Section: Discussionmentioning
confidence: 99%
“…Traits contributing to yield and grain quality are usually antagonistic to each other, and when applying various modifications in agrotechnology, this should be taken into consideration. The forms and amounts of available mineral nutrients in the soil can cause significant changes in the growth character and biochemical composition of plants [55]. According to Gu et al [56], the availability of N reduces oil concentration, while the application of K increases oil content.…”
Section: Discussionmentioning
confidence: 99%
“…Sharma et al [68] collected 523 QTL to carry out meta-analysis for silage quality traits in maize and also achieved substantial reductions in the size of the confidence intervals. Sethi et al [19] conducted meta-analysis for grain quality and yield-related traits with 2974 initial QTL in maize and obtained a total of 68 MQTL with a mean physical confidence interval of 3.30 Mb. Concerning drought tolerance, Loni et al [16] employed meta-analysis in foxtail millet with 448 initial QTL and identified 41 MQTL.…”
Section: Characteristics Of Qtl and Mqtl For Drought Tolerance In Maizementioning
confidence: 99%
“…The physical position of significant marker-trait associations (MTAs) from these studies was compared with the physical positions of the MQTL. The overlapping MTAs or adjacent MTAs (within 500kb upstream and downstream of the MQTL regions) were considered as verification of the MQTL [19].…”
Section: Verification Of Mqtl With Gwas Studiesmentioning
confidence: 99%
See 2 more Smart Citations